2016
DOI: 10.7903/ijecs.1448
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Website Quality Features and Cognitive Absorption on Social Network Site Usage: A Cross-National Study

Abstract: Social network sites (SNSs) have become an essential interpersonal communication tool, and the number of global SNSs users is increasing at an astonishing rate. To fill the research gap on SNSs, this study examined the rarely discussed influence of website quality features and cognitive absorption on SNS acceptance. This cross-sectional study focused on comparing 250 users from Taiwan and 200 users from Indonesia to contribute to the growing field of information system (IS) and information technology (IT) lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Based on the S-O-R model, the factors of the stimulus are information quality, system quality and virtual object characteristics; we posited the users fit (cognitive fit and emotional fit) as the organism and user satisfaction and intention of continued use as the responses. Hsu et al (2016) believed that if users received high-quality information (i.e. high quality in terms of integrity, accuracy, diversity and reliability), they would have a more fruitful and pleasant experience, which would have a greater effect on the cognition of users.…”
Section: The Fit Of Real and Virtual World Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the S-O-R model, the factors of the stimulus are information quality, system quality and virtual object characteristics; we posited the users fit (cognitive fit and emotional fit) as the organism and user satisfaction and intention of continued use as the responses. Hsu et al (2016) believed that if users received high-quality information (i.e. high quality in terms of integrity, accuracy, diversity and reliability), they would have a more fruitful and pleasant experience, which would have a greater effect on the cognition of users.…”
Section: The Fit Of Real and Virtual World Integrationmentioning
confidence: 99%
“…Systems depend on user demand, and the stability, safety, privacy and simplicity of the system are all essential factors (Ahn et al, 2007). As game technologies have rapidly advanced, the most basic system developments have been accompanied by complex elements, such as visual and audio assistance, global positioning systems for users and VR or AR (Hsu et al, 2016). These elements intensify the quality of people's cognition of the system.…”
Section: The Fit Of Real and Virtual World Integrationmentioning
confidence: 99%
“…Individuals' continued intention to use the online learning system can be predicted by analyzing these vital aspects [2], [29], [34]. Therefore, design quality is crucial to create an engaging environment that easily supports learners accessing the preferred information [41]. Huarng et al [42] argue that individuals are attracted by interface design, and their experience encourages them to decide whether to continue using it or not.…”
Section: Design Characteristics As Environmental Stimulimentioning
confidence: 99%
“…After the rise of multimedia, CA efficacy has been widely applied in technology media acceptance research and has been found to be a key antecedent for acquiring a deeper understanding of the formation of user beliefs and IS/IT usage intention. Examples include e-learning and mobile learning (Reychav and Wu, 2015a, 2015b; Shah and Soror, 2019; Cheng, 2022), mobile instant messaging (Hou and Shang, 2018; Hou et al , 2019) and social networking site (Hsu et al , 2016; Hsu and Lin, 2017; Guinaliu-Blasco et al , 2019). In the e-learning and social network context, Cheng (2022) found that CA positively influences cloud-based e-learning continuance intention and performance outcomes.…”
Section: Hypotheses and Research Frameworkmentioning
confidence: 99%